Terrorism and organised crime: The system of “permanent conflict” in the Sahel. - Cuneo, Palmerino (Journal of the Spanish Institute for Strategic Studies, 2019)
The fundamental tenets of International Relations on post-modernity, power and sovereignty have become more complex as a result of globalisation and growing interdependence. Where power becomes disseminated and diluted, sovereignty is shared, and the lines between competition, cooperation and conflict become blurred. In the context of structural conflict in the Sahel, the old relational patterns are no longer adequate. A perspective is needed that allows placing the phenomenon of terrorism within the current geopolitical dimension where complex relationships of mutual dependence also apply to illicit transnational actors: terrorism and organised crime.